Foreign Manufacturing Companies and Social Changes in Indonesia - Efa Ida Amaliyah; Nuskhan Abid; Ulya (Journal of Social Transformation and Regional Development, 2022)
Jepara, one of regency in Central Java, Indonesia, has experienced a wave of changes caused by modernization and globalization that occurred at the national level, which resulted in changes at the local level. The changes have resulted in dynamics and shifts in several fields, such as spatial, social, economic, and cultural fields. This paper tries to see the changes in society due to globalization with the entry of Foreign Manufacturing Companies (FMC) in Indonesia. These changes occurred in several fields, such as economic, social, and cultural. This research was conducted on the people of Jepara, who started the arrival of FMC within a decade. By using qualitative research and an ethnographic approach by conducting in-depth observations and interviews with the community around the factory and local leaders. The results show that the entry of FMC around 2013 brought changes in spatial planning, with much land being converted. In addition, a significant change for the people of Jepara is the absorption of many productive workers, ultimately increasing their economy. However, the existence of the FMC also provides a lifestyle change, namely by changing the culture of the community, especially in socializing with the surrounding environment, hedonism, and disorder in driving. The above changes should be a serious concern from the relevant agencies or institutions so that Jepara becomes a conducive and adaptive area as an industrial area without losing the local wisdom of its people, namely a society that is always simple, religious, and optimistic.